KAJIAN YURIDIS PELAKSANAAN TUKAR GULING TANAH WAKAF AKIBAT PENGADAAN TANAH UNTUK PEMBANGUNAN JALAN TOL SOLO-SEMARANG (Studi Di Kabupaten Boyolali) - HARDIYANTO, BAMBANG (Dinamika Hukum, 2018)
The purpose of this study is to: 1) Review and analyse the mechanisms of implementation of Exchange due to the procurement of the Waqf land spit of land for the construction of the highway in the village of Mojolegi sub-district of the terrace and the village of Denggungan Sub-district Banyudono Boyolali Regency. 2) review and analyze the obstacles that occur in the implementation of the exchange of land endowments due to scroll the procurement of land for the construction of the highway in the village of Mojolegi sub-district of the terrace and the village of Denggungan Sub-district Banyudono Boyolali Regency.The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of skunder. Engineering data collection using the study interview, the library and study the documents. To analyze the data, the researchers used a qualitative descriptive methods of analysis.Based on the research results obtained the conclusion that the mechanism of implementation of the result of the Waqf land spit switch the procurement of land for the construction of the highway in the village of Mojolegi and the village of Denggungan Sub-district Banyudono Boyolali Regency Terrace Sub implemented with reference to the provisions of the presidential Regulation number 3 of the year 2016 on the acceleration of project implementation, National execution so conveniently located changes the status of the Waqf property affected by the procurement of land for the construction of toll roads tend to conflict with the provisions of legislation regulating the mechanism of change of status of property endowments. Barriers that occur in the implementation of the exchange of land endowments due to scroll the procurement of land for the construction of the highway in the village of Mojolegi sub-district of the terrace and the village of Denggungan Sub-district Banyudono Boyolali Regency are: (1) Internal factors that is most great Nazhir still less understanding about the basic tasks and functions related changes the status of the Waqf Property affected by the highway as well as the active role and coordination of the related parties include: Nazhir, KUA, Religious Ministry (Central, provincial, city of Semarang), BWI, and Semarang toll road, PPK, national land Agency and the team Implementing the procurement of land where the maximum yet in the settlement changes the status of the Waqf Property affected by the highway. (2) external factors that is having trouble finding a replacement property land endowments affected the appropriate toll road development, both in terms of the value of the loss, dressing side reviewed the Location and designation of utilization of Space. Keywords: Swap spit of land endowments, the procurement of land for the public interest.